A further investigation of leaf sesquiterpene variation in relation to herbivory in two Brazilian populations of Copaifera langsdorfii - Macedo, Cynthia A.; Langenheim, Jean H. (Biochemical systematics and ecology, 1989)
Herbivory, leaf sesquiterpene concentrations and yield were compared over time within and between two populations of Copaifera langsdorfiiin a southeastern Brazilian woodland. At one site (LA) immature leaves, which have extremely low sesquiterpene yields, were attacked by a gelechiid leaf-tier; at the second site (SC) only mature leaves, which have higher sesquiterpene yields, were attacked by an oecophorid leaf-tier. LA trees, which have been subject to at least two herbivore outbreaks during the last five years, are less vigorous and have higher leaf sesquiterpene yields in their mature leaves compared to SC trees. SC trees, which have supported a relatively stable and lower herbivore (oecophorid) population since 1981, have more variable concentrations of cyperene, γ-muurolene and caryophyllene oxide compared to LA trees. Higher yields and more variable concentrations of certain compounds may be important in restricting herbivores such as gelechiids and oecophorids on C.langsdorfiiand may partially be a result of historically different intensities and types of herbivory.